Budesonide as induction therapy for incomplete microscopic colitis: A randomised, placebo‐controlled multicentre trial. Issue 7 (20th August 2021) - Münch, Andreas; Mihaly, Emese; Nagy, Ferenc; Madisch, Ahmed; Kupčinskas, Juozas; Miehlke, Stephan; Bohr, Johan; Bouma, Gerd; Guardiola, Jordi; Belloc, Blanca; Shi, Chunliang; Aust, Daniela; et al.
Abstract: Background and aims: Incomplete microscopic colitis (MCi) is a subtype of microscopic colitis (MC). Budesonide is recommended as a first‐line treatment for MC. However, randomised trials on efficacy of treatment in MCi are missing. We therefore performed a randomised, placebo‐controlled trial to evaluate budesonide as induction therapy for MCi. Methods: Patients with active MCi were randomly assigned to either budesonide 9 mg once daily or placebo for 8 weeks in a double‐blind, double‐dummy design. The primary endpoint was clinical remission, defined as a mean of <3 stools/day and a mean of <1 watery stool/day in the 7 days before week 8. Results: Due to insufficient patient recruitment, the trial was discontinued prematurely. The intention‐to‐treat analysis included 44 patients (21 budesonide and 23 placebo). The primary endpoint of clinical remission at week 8 was obtained by 71.4% on budesonide and 43.5% on placebo ( p = 0.0582). All clinical secondary endpoints were in favour of budesonide. Budesonide decreased the number of soft or watery stools (16.3 vs. 7.7, p = 0.0186) and improved health‐related quality of life for all four dimensions of the short health scale. Adverse events with a suspected relation to study drug were reported in one patient in the budesonide group and two patients in the placebo group. Neither serious nor severe adverse events occurred during the double‐blind phase. Conclusions: Budesonide decreased the frequency of soft or watery stools and improved the patients' quality of life significantly in MCi, but the primary endpoint was not met due to the low sample size (type 2 error). Budesonide was safe and well tolerated during the 8‐weeks treatment course.